2017
DOI: 10.1302/2046-3758.64.bjr-2016-0245.r1
|View full text |Cite
|
Sign up to set email alerts
|

The segment-dependent changes in lumbar intervertebral space height during flexion-extension motion

Abstract: ObjectivesMany studies have investigated the kinematics of the lumbar spine and the morphological features of the lumbar discs. However, the segment-dependent immediate changes of the lumbar intervertebral space height during flexion-extension motion are still unclear. This study examined the changes of intervertebral space height during flexion-extension motion of lumbar specimens.MethodsFirst, we validated the accuracy and repeatability of a custom-made mechanical loading equipment set-up. Eight lumbar speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…In vitro cadaveric tests have examined the biomechanical responses of the disc to external loads using various mechanical loading equipment setups. Fu et al [13] measured the segment-dependent changes in lumbar intervertebral space height during exion-extension motion in a custom-made mechanical loading equipment set-up. The author found that the changes in disc height at L4/5 were different from those at the L3/4 during exionextension motion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro cadaveric tests have examined the biomechanical responses of the disc to external loads using various mechanical loading equipment setups. Fu et al [13] measured the segment-dependent changes in lumbar intervertebral space height during exion-extension motion in a custom-made mechanical loading equipment set-up. The author found that the changes in disc height at L4/5 were different from those at the L3/4 during exionextension motion.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have aimed to examine the lumbar complex structures and biomechanical behavior of the lumbar discs using both in vitro and in vivo approaches. [1][2][3][4][5][6][7][8][9][10][11][12][13]For example, sagittal magnetic resonance (MR) has been used to study the height of different disc components in the non-weight-bearing supine position, and to compare the segmental dependence. [14] In vivo motion of the lumbar spine has often been evaluated by using three-dimensional (3D) uoroscopic imaging and CT or MRI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the influence of tensile stress on the AF the disc subsequently becomes stiffer to enhance stability and support. The range of motion in normal physiological load bearing in a FSU varies directly with the vertebral height of disc and indirectly with the transverse diameter of the body of the vertebra [16,17]. Both vertebrae as well as IVDs are largest and thickest in the lumbar region making it a strong enough to bear the normal load in an erect posture.…”
Section: Anatomy and Biomechanics Of Lumar Fsumentioning
confidence: 99%
“…Therefore, accuracy in MRI reports is very important. One of the effective factors in the accuracy of MRI reports is the medical history of patients in radiology request forms, which can be helpful or, on the other hand, lead to bias and haste in the writing of reports by residents, especially in educational centers with a high workload, so that the residents may use the histories and refrain from classic and systematic reading of MRI images, which would increase the number of false negative and false positive cases and, contrary to popular belief, reduce the accuracy of the reports [9], [10], [11], [12]. The radiologist does not have direct contact with the patient for medical history and physical examination, and thus, an incomplete and inaccurate history may also be misleading [13].…”
Section: Introductionmentioning
confidence: 99%